A Shift From Non-operative Care to Surgical Fixation of Pediatric Humeral Shaft Fractures Even Though Their Severity Has Not Changed - Hannonen, Juuli; Sassi, Elina; Hyvönen, Hanna; Sinikumpu, Juha-Jaakko (Frontiers in Pediatrics, 2020)
Introduction: Humeral shaft fractures have traditionally been treated non-operatively due to their good union and low rate of functional impairment. In the recent years, upper extremity fractures and their operative treatment have increased in children. Nevertheless, the trends of humeral shaft fractures are not clear. Materials and Methods: All children aged <16 years, with a humeral shaft fracture in the geographical catchment area of Northern Finland Hospital District, with a yearly child population-at-risk of 86 000 from the year 2001 until the end of 2015 were included. There were 88 cases, who comprised the study population. Radiographs were available of all. Injury, patient, and treatment characteristics were reviewed from hospital databases. Results: There was an increasing trend of surgical fixation of humeral shaft fractures during the 15 years' study period (β = 1.266, 95% CI 0.17 to 2.36, p = 0.035). However, we found no patient or fracture-related reasons that could have explained the increasing trend of surgical care. Comminuted fracture increased the risk of operative treatment 8-fold (Odds Ratio, OR 7.82, 95% CI 1.69 to 36.3, p = 0.009). Higher age, greater angular deformity or greater diameter of the humerus were not associated with the increased operation risk. Conclusions: The treatment philosophy concerning pediatric humeral shaft fractures has presented a shift from conservative care to surgical fixation. To authors' understanding there is not evidence supporting the increasing rate of osteosynthesis.